2013
DOI: 10.1002/etc.2145
|View full text |Cite
|
Sign up to set email alerts
|

INVESTIGATION OF THE TOXICOKINETICS OF PETROLEUM HYDROCARBON DISTILLATES WITH THE EARTHWORM EISENIA ANDREI

Abstract: The Canada-wide standards for petroleum hydrocarbons in soils regulate petroleum hydrocarbons based on four distillate ranges: F1 (C6-C10), F2 (>C10-C16), F3 (>C16-C34), and F4 (>C34). Previous toxicity tests with earthworms and F2, as well as two subfractions of F3, F3a (>C16-C23) and F3a (>C23-C34), indicate that test durations might not be sufficiently long to reach threshold effect concentrations, likely because of the differing toxicokinetics for each distillate. A study was conducted to determine the tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Inclusion of an earthworm property (SSAlipid) as an additional model input slightly improved the model fit for bulk soil-based elimination rate constants ( k out , R 2 = 0.88). The dependence of elimination rate constants on hydrophobicity (log K ow or TPSA) is consistent with previous studies, which demonstrated that the strong binding of hydrophobic compounds to earthworm lipids may retard elimination. For example, Matscheko et al observed a strong negative correlation between elimination rate constants and log K ow (which itself is correlated negatively to TPSA) for polycyclic aromatic hydrocarbons and polychlorinated biphenyls.…”
Section: Resultssupporting
confidence: 91%
“…Inclusion of an earthworm property (SSAlipid) as an additional model input slightly improved the model fit for bulk soil-based elimination rate constants ( k out , R 2 = 0.88). The dependence of elimination rate constants on hydrophobicity (log K ow or TPSA) is consistent with previous studies, which demonstrated that the strong binding of hydrophobic compounds to earthworm lipids may retard elimination. For example, Matscheko et al observed a strong negative correlation between elimination rate constants and log K ow (which itself is correlated negatively to TPSA) for polycyclic aromatic hydrocarbons and polychlorinated biphenyls.…”
Section: Resultssupporting
confidence: 91%